Zein-based blend coatings: Impact on the quality of a model cheese of short ripening period - Pena-Serna, Carolina [UNESP]; Barretto Penna, Ana Lucia [UNESP]; Lopes Filho, Jose Francisco [UNESP] (Elsevier B.V., 2016)
Two biodegradable zein-based blend coatings were evaluated according to the impact on the quality of the Minas Padrao cheese throughout a storage period of 56 days. Throughout the storage, the biodegradable-coated cheese samples showed similar physicochemical characteristics in comparison to unpackaged and plastic-packaged cheese samples in terms of chlorides, ash, protein and acidity. Besides that, cheese samples with biodegradable coatings exhibited ca. 30% lower weight loss and avoided microbiological contamination for more than 50 days when compared to unpackaged cheese samples that exhibited contamination after 21 days. Although cheese samples with biodegradable coatings exposed a positive behavior in comparison to unpackaged cheeses, some challenges remain and require further studies. For instance, as a consequence of the moisture loss, after 28 days of storage, the biodegradable-coated cheeses were 124% harder, displayed 30% less proteolysis and more than 50% change in color surface than cheese samples with polyethylene packaging. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable coating; Ripened cheese; Zein-based material; Texture profile analysis; Proteolysis